(untitled) (Journal of human and social sciences, 2017)
This study examines the use of grammar in the explanation of Hadith by Sheikh Muhammad bin Abdul Hadi Al-Sindi (d. 1138 AH) through his commentary on Sahih Al-Bukhari. The research aims to highlight the role of grammatical rules in serving the meanings of Prophetic traditions, as Al-Sindi relied on grammar as a tool to interpret Hadith without bias towards any particular grammatical school. The study addressed examples of Al-Sindi’s grammatical opinions, such as his rejection of the preposition "ب" (ba) denoting partiality, the permissibility of jussive mood with "لن" (lan), the addition of the adverb "حيث" (haythu) to clauses, and the use of the causal "ب". The study concluded that Al-Sindi possessed a strong linguistic sense and broad knowledge of grammarians’ views, which aided him in providing precise explanations of Hadith. It also demonstrated the importance of commentaries and explanations in enriching linguistic and grammatical sciences.